2023
DOI: 10.1002/wjo2.118
|View full text |Cite
|
Sign up to set email alerts
|

Late recurrence in surgically managed pediatric atypical mycobacterial lymphadenitis: A case report and review of the literature

Abstract: ObjectiveThe purpose of this study is to identify existing literature on recurrent atypical mycobacterial cervicofacial lymphadenitis to augment our understanding of a unique patient who presented to our tertiary‐care center 5‐years posttreatment with recurrence following curettage.Data SourcesOVID Medline, Scopus, and Web of Science.MethodsA literature search was conducted yielding 49 original articles which were screened twice by two independent reviewers resulting in 14 studies meeting inclusion criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recurrence has been reported up to seven years after the original treatment [7,43], but rates vary widely based on treatment modality used. One study of 117 children reported a rate of 10% in patients treated with a nonsurgical approach from 1 to 4 years after initial resolution [44].…”
Section: Post-operative Care and Surveillancementioning
confidence: 99%
“…Recurrence has been reported up to seven years after the original treatment [7,43], but rates vary widely based on treatment modality used. One study of 117 children reported a rate of 10% in patients treated with a nonsurgical approach from 1 to 4 years after initial resolution [44].…”
Section: Post-operative Care and Surveillancementioning
confidence: 99%